Spatial enactments in emancipatory higher education pedagogies - Postma, Dirk (Critical Studies in Teaching and Learning, 2023)
The focus on the role of space in social sciences provides new perspectives on the possibilities for emancipatory pedagogies in higher education. The posthumanist insight into heterogeneous agency draws attention to the agential roles of spaces. The implications of spatial agency are investigated through a diffractive reading of Rancière’s emancipatory pedagogy with a spatial typology. A spatial typology originating from the social studies of science distinguishes between regional, network, fluid and fire spaces. Whereas banking education could be associated with regional spaces, progressive and critical pedagogies are closer to fluid spaces. In contrast, it is shown how the emancipatory pedagogy of Rancière is made possible through the interference of regional and fire spaces. The spatial analysis draws on the powerful effects of interferences (or diffractions). The significant finding of this investigation is that the possibility for emancipation is not ascribed to the spaces as such, but to the interference of regional-and fire spaces. Powerful effects are possible when regional spaces enable an awareness of the equality of intelligence and fire spaces the transformation of the world.